Mechanical Excavation for the Tunnels in Soft Rock - Inoue T; Takahashi N (The Australasian Institute of Mining and Metallurgy, 1987)
To construct the accessing railroad line to the northern portal of Seikan Undersea Tunnel, nine tunnels amounting 7.4km in their total length were excavated through soft mudstones of young- er tertiary era with use of smaller-sized mechanic al excavators. Rocks were classified in four classes to which the tunnel support was designed respectively. Of several combinations of driving equipments stu- died comparatively, the method using the mechani- cal excavators was estimated to be the best choi- ce. The efficiency of the excavator was traced in every construction section and the data colle- cted was reviewed numerically. The result showed that the efficiency of the excavator dropped wh- ere the rocks were as hard as over 200kg/crif for compressive strength. And a few technigues in tunnelling i.e. contr- olling dusts in shotcreting, lattice arch, evaluati- ng measured deformations were tested and review- ed too.